2011
DOI: 10.1038/ajg.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Branched-Chain Amino Acids Supplementation in Patients With Cirrhosis and a Previous Episode of Hepatic Encephalopathy: A Randomized Study

Abstract: Diet supplementation with BCAA after an episode of HE does not decrease recurrence of HE. However, supplementation with BCAA improves minimal HE and muscle mass. Identification of risk factors for recurrence of HE may allow the development of new preventive therapies that could decrease the neuropsychological sequelae of repeated episodes of HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 32 publications
1
134
0
7
Order By: Relevance
“…Aminoacidi a catena ramificata: diminuiscono i livelli di aminoacidi aromatici coinvolti nelle alterazioni della neurotrasmissione in corso di EE e riducono il catabolismo proteico e la conseguente produzione di ammonio da parte del tessuto muscolare. Le evidenze della loro utilità clinica sono limitate [100,101], sebbene ne sia stata dimostrata l' efficacia, in particolare, nell'EE precipitata dal sanguinamento gastrointestinale [103]. L-ornitina-L-aspartato (LOLA): recenti evidenze sostengono l'utilizzo del LOLA, in quanto si è dimostrato in grado di diminuire i livelli di ammonio, migliorare lo stato mentale e le performace cognitive dei pazienti con cirrosi epatica [104,105].…”
Section: Terapia Domiciliareunclassified
“…Aminoacidi a catena ramificata: diminuiscono i livelli di aminoacidi aromatici coinvolti nelle alterazioni della neurotrasmissione in corso di EE e riducono il catabolismo proteico e la conseguente produzione di ammonio da parte del tessuto muscolare. Le evidenze della loro utilità clinica sono limitate [100,101], sebbene ne sia stata dimostrata l' efficacia, in particolare, nell'EE precipitata dal sanguinamento gastrointestinale [103]. L-ornitina-L-aspartato (LOLA): recenti evidenze sostengono l'utilizzo del LOLA, in quanto si è dimostrato in grado di diminuire i livelli di ammonio, migliorare lo stato mentale e le performace cognitive dei pazienti con cirrosi epatica [104,105].…”
Section: Terapia Domiciliareunclassified
“…Although oral BCAA supplementation after an episode of hepatic encephalopathy does not decrease recurrence of hepatic encephalopathy, it relieves minimal hepatic encephalopathy and increases muscle mass. [14]. It is also associated with reduced incidence of HCC in patients with Child-Pugh A cirrhosis [15] and in patients with a BMI of 25 kg/m 2 or higher [16].…”
Section: Diagnosis Of Liver Cirrhosismentioning
confidence: 99%
“…It prevents progressive hepatic failure, improves surrogate markers, improves perceived health status [210], and improves event-free survival in patients with decompensated cirrhosis with an adequate daily food intake [10]. It relieves minimal hepatic encephalopathy, improves neuropsychological test scores, and increases the muscle mass [14]. It may inhibit hepatic carcinogenesis in patients with compensated cirrhosis with a serum albumin level of less than 4.0 g/dL [11].…”
Section: Cq: Is Albumin Infusion Effective For Treatment Of Cirrhoticmentioning
confidence: 99%
“…Some studies have demonstrated improvements in HE with improved nutritional parameters. Unfortunately, BCAA preparations have important limitations: poor palatability, high cost, and lack of availability in Turkey (22,23). Moreover, alterations in lipid metabolism occur by several mechanisms, and guidelines suggest that fat should be provided at a minimum of 25%-30% of the total daily calories (8,19).…”
Section: Macronutrientsmentioning
confidence: 99%